High performance hybrid Al2O3/poly(vinyl alcohol-co-ethylene) nanofibrous membrane for lithium-ion battery separator. (10th September 2015) - Liu, Qiongzhen; Xia, Ming; Chen, Jiahui; Tao, Yifei; Wang, Yuedan; Liu, Ke; Li, Mufang; Wang, Wenwen; Wang, Dong
Graphical abstract: Abstract: High performance Al2 O3 @NFs/PET/NFs separator possessing hierarchically three-dimensional tortuous structure has been developed to promote the cell performance of NFs/PET/NFs separator. The separator comprises a poly (ethylene terephthalate) (PET) nonwoven sandwiched between two poly (vinyl alcohol- co -ethylene) (PVA- co -PE) nanofirous membrane and inorganic Al2 O3 coating layers on both sides for surface modification. The Al2 O3 @NFs/PET/NFs separator shows high porosity and impressively superior electrolyte affinity, thus resulting in higher ion conductivity, smaller interfacial resistance, excellent rate capabilities and cycling performance, compared to the NFs/PET/NFs separator and a commercial PP/PE/PP separator. This high cell performance can be ascribed to synergetic effects of inherent good hydrophilicity of γ -Al2 O3 nanopowder coatings and well-designed tortuous nanoporous structure of NFs/PET/NFs membrane. This study suggests that the Al2 O3 @NFs/PET/NFs separator is a desirable alternative to commercial lithium-ion battery separators, especially promising for large-sized lithium batteries.